2014
DOI: 10.1177/0957926514556208
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of metaphors: Phylogeny of oil slick cartoons in Spanish press

Abstract: The main purpose of this article is to analyze the evolution of a metaphor set over time. By studying cartoons about the oil slick caused by the Prestige oil tanker in 2002 on Spanish shores and the subsequent court decision in 2013, we observe a progressive metaphor diversification and evolution, with the oil slick as an old common trait. Additionally, using basic cladistical methods, we propose a phylogenetic tree for the metaphor set, from a common ancestor to the subsequent diversification regarding news c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…In a previous article, I suggested that metaphors underwent an intense process of selection and adaptation, that sometimes we could even find a speciation process (Domínguez, 2015b). From an ancestral metaphor, different evolutionary lines are originated to colonize new communicative niches within a larger media habitat (Domínguez, 2015a). The most successful metaphors become memes that quickly spread among the population.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In a previous article, I suggested that metaphors underwent an intense process of selection and adaptation, that sometimes we could even find a speciation process (Domínguez, 2015b). From an ancestral metaphor, different evolutionary lines are originated to colonize new communicative niches within a larger media habitat (Domínguez, 2015a). The most successful metaphors become memes that quickly spread among the population.…”
Section: Discussionmentioning
confidence: 98%
“…There is a feedback between the new niche and the metaphors that adapt to new variations in the medium (or are recontextualized). Even when there is an exaptation (Domínguez, 2015a), and a metaphor with an original meaning adopts new rhetorical content. All this evolutionary process continues while the news remains valid: that is, while there is an information need and an interpretative effort in society.…”
Section: Conclusion: the Eco-evolutionary Metaphoric New Synthesismentioning
confidence: 98%
“…Certainly, the use of metaphors must have provided a positive communicative fitness to the first groups of humans who used them, and therefore a greater biological efficiency resulting in a selective advantage over other groups or even species. Human culture is full of old-fashioned metaphors, to be found in ancient texts, proverbs and traditional tunes and songs as a kind of forever-extinct fossil communicative strategy (Domínguez, 2015). As Vico wrote in New Science (1744), showing how much the beginning of language was strongly metaphoric, 'the first human were poets' ('.…”
Section: Conclusion: the Metaphorical Speciesmentioning
confidence: 99%
“…In some cases, a surprising adaptive diversification occurs, and an old metaphor adapts to a new and unexpected communicative circumstance in a generative metaphor process (Schön, 1993): a reuse of the metaphor across context or recontextualisation (Linell, 2009;Semino et al, 2013). Therefore, in many occasions a phylogenetic monitoring process can be followed, starting with a primal metaphor and ending in a number of new phyla, which are related but clearly identifiable (Domínguez, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Cartoons are a very useful tool to analyse social reality. Graphic humour is a very powerful way of conveying news, and portraying its most compelling and outstanding aspects to the public (Domínguez, 2014(Domínguez, , 2015a(Domínguez, , 2015b. Several studies show how public opinion is better captured in cartoons, especially in relation to particularly contested issues.…”
Section: Introductionmentioning
confidence: 99%